Three new species of Diaphorus Meigen (Diptera: Dolichopodidae) from Tibet - Liu, Ruosi; Wang, Mengqing; Yang, Ding (Zootaxa, 2015)
The species of Diaphorus Meigen from Tibet are reviewed. Previously only one species, Diaphorus xizangensis Yang & Grootaert, was known to occur in Tibet. The following three species are described as new to science: Diaphorus baheensis sp. nov., Diaphorus longrenensis sp. nov. and Diaphorus nigripedus sp. nov. Diaphorus anatoli Negrobov is recorded from Tibet for the first time. A key to the species of Diaphorus from Tibet and the Himalayan area is presented.